EFFECT OF LEBAZOL CYTMULATORINE ON COTTON DRESSING (British Journal of Global Ecology and Sustainable Development, 2022)
In subsequent years, many stimulants are being tested in the care of the goose, and those that have given a positive result are widely introduced into practice. The test work of such preparations as lebozol PK, Lebozol Mags SK, Lebozol potassium 450, Lebozol calcium-Forte, Lebozol Frut mix, Lebozol PK Max, Lebozol Quadro mix, Lebozol Magfos, Nutriplant 8-8-6) and Aminozol PK, whose composition is rich in micro and Macroelements, and Macroelements lebozol PK when treated with the drugs Max, lebozol magfos, nutriplant 8-8-6, lebozol boron, lebozol Mags SK, lebozol potassium 450, Lebozol Quadro mix and Aminozol, compared to the control option, a high cotton yield of 1.2-6.5 ts/Ha was achieved.